PENTINGNYA RESTORATIVE JUSTICE DALAM KONSEP IUS CONSTITUENDUM - Zico Junius Fernando (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: The State of Indonesia is a state of law, the affirmation of this can be seen in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. The settlement of cases through the judicial system which results in a court verdict is law enforcement towards the slow path. This is because law enforcement through a long-distance, through various levels starting from the Police, Attorney General's Office, District Court, High Court and even to the Supreme Court which ultimately has an impact on the accumulation of cases which are not small in number in the Court and not to mention other effects. For this reason, it is necessary to proceed with the steps to compile invitations concerning the rights and obligations of citizens in the context of implementing the Pancasila and the 1945 Constitution. Renewal of the Criminal Code by its authors is positioned as the foundation for building a national criminal law system. Related to the Political Law of Criminal Law Renewal in the upcoming National Criminal Law there is a concept known as the Restorative Justice concept. Restorative Justice involves restoring relations between the victim and the perpetrator. The restoration of this relationship can be based on mutual agreement between the victim and the perpetrator. The victim can convey about the loss he suffered and the perpetrator was given the opportunity to make it up, through compensation mechanisms, peace, social work, and other agreements. Keywords: Restorative Justice; Legal Reform; RKUHP